Water – India’s Burning Problem Vis-à-vis Hydropower – Nepal’s Burning Desire - Pun, Santa Bahadur (NCWA Annual Journal, 2025)
Having been badly stung by the one-sided unequal 1954 Kosi and 1959 Gandak treaties with India, Nepal had the World Bank involved in the development of the Karnali Chisapani Multipurpose Project. At the same time, Nepal also sought multilateral/bilateral assistance in the development of her medium rivers: Kankai, Kamala, Bagmati, West Rapti and Babai. Unfortunately, Nepal had to undergo tough negotations with India on every medium river project. This is because India’s greatest burning problem is freshwater – water to drink/ bathe and produce food for 47% of India’s gargantuan 1.4 billion people living in the Ganges Basin. A running commentary of the struggles on the Babai Irrigation Project has been related in this article. But for reasons best known to our politicians and bureaucrats, Nepal is ceaselessly beating her war drums to produce 28,500 MW by 2035. Is Nepal barking up the right tree? That is the million-dollar question.